2005
DOI: 10.1152/ajpregu.00127.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of periconceptional nutrition on maternal and fetal leptin and fetal adiposity in singleton and twin pregnancies

Abstract: It has been proposed that maternal nutrient restriction may alter the functional development of the adipocyte and the synthesis and secretion of the adipocyte-derived hormone, leptin, before birth. We have investigated the effects of restricted periconceptional undernutrition and/or restricted gestational nutrition on fetal plasma leptin concentrations and fetal adiposity in late gestation. There was no effect of either restricted periconceptional or gestational nutrition on maternal or fetal plasma leptin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 35 publications
2
21
0
2
Order By: Relevance
“…It would be interesting to determine whether the low PPAR␥ abundance contributes to a decreased insulin sensitivty in the postnatal visceral fat depot after the transition from the fetal environment, where the circulating free fatty acid concentrations are low, to the postnatal environment, where there are higher free fatty acid concentrations. The lack of change in the expression of leptin and adiponectin in the PCUN and PIUN groups is consistent with our earlier findings in PCUN fetuses (11) and suggests that leptin expression in fetal fat is not programmed specifically by exposure to poor maternal nutrition around the time of conception. AMPK has been shown to play an important role in stimulating glucose uptake and fatty acid ␤-oxidation in liver and skeletal muscle (22,42).…”
Section: E938supporting
confidence: 91%
See 1 more Smart Citation
“…It would be interesting to determine whether the low PPAR␥ abundance contributes to a decreased insulin sensitivty in the postnatal visceral fat depot after the transition from the fetal environment, where the circulating free fatty acid concentrations are low, to the postnatal environment, where there are higher free fatty acid concentrations. The lack of change in the expression of leptin and adiponectin in the PCUN and PIUN groups is consistent with our earlier findings in PCUN fetuses (11) and suggests that leptin expression in fetal fat is not programmed specifically by exposure to poor maternal nutrition around the time of conception. AMPK has been shown to play an important role in stimulating glucose uptake and fatty acid ␤-oxidation in liver and skeletal muscle (22,42).…”
Section: E938supporting
confidence: 91%
“…These findings are important, as the thermogenic capacity of brown fat and the insulin sensitivity of visceral fat are important determinants of the risk of developing obesity and an insulin resistance phenotype in later life. pregnancy; nutrition; programming; metabolism A RANGE OF EXPERIMENTAL AND CLINICAL STUDIES has shown that poor maternal nutrition experienced around the time of conception or during pregnancy, placental insufficiency, and being of low birth weight are each associated with an increase in visceral fat mass in postnatal life (5,9,11,17,21,27,30,31). Interestingly, exposure to a poor nutrient supply in early pregnancy, such as which occurred in the Dutch Winter Famine of 1944Famine of -1945, in the absence of a change in birth weight resulted in increased adiposity in later life (38, 39).…”
mentioning
confidence: 99%
“…Par exemple, la sous-nutrition chez la brebis gestante au cours du premier tiers de la gestation est associée avec une accumulation excessive de graisse en fin de gestation [57,58]. Chez le rat, une sous-nutrition maternelle en période préimplantatoire induit des anomalies des blastocystes et une hypertension artérielle dans la descendance [59].…”
Section: Effets Périconceptionnelsunclassified
“…Aside from the recent references most familiar to the authors (1-3, 9, 12, 16 -18, 20, 21, 24, 31, 32, 37, 39, 44 -46) are many others, including special issues of Trends in Endocrinology and Metabolism (vol. 13,2002) and British Medical Bulletin (vol. 60, 2001).…”
mentioning
confidence: 99%